Acute oxygen sensing by vascular smooth muscle cells - Moreno-Domínguez, Alejandro; Colinas, Olaia; Smani, Tarik; Ureña, Juan; López-Barneo, José (Frontiers in Physiology, 2023)
An adequate supply of oxygen (O2) is essential for most life forms on earth, making the delivery of appropriate levels of O2 to tissues a fundamental physiological challenge. When O2 levels in the alveoli and/or blood are low, compensatory adaptive reflexes are produced that increase the uptake of O2 and its distribution to tissues within a few seconds. This paper analyzes the most important acute vasomotor responses to lack of O2 (hypoxia): hypoxic pulmonary vasoconstriction (HPV) and hypoxic vasodilation (HVD). HPV affects distal pulmonary (resistance) arteries, with its homeostatic role being to divert blood to well ventilated alveoli to thereby optimize the ventilation/perfusion ratio. HVD is produced in most systemic arteries, in particular in the skeletal muscle, coronary, and cerebral circulations, to increase blood supply to poorly oxygenated tissues. Although vasomotor responses to hypoxia are modulated by endothelial factors and autonomic innervation, it is well established that arterial smooth muscle cells contain an acute O2 sensing system capable of detecting changes in O2 tension and to signal membrane ion channels, which in turn regulate cytosolic Ca2+ levels and myocyte contraction. Here, we summarize current knowledge on the nature of O2 sensing and signaling systems underlying acute vasomotor responses to hypoxia. We also discuss similarities and differences existing in O2 sensors and effectors in the various arterial territories.